Macrophage-preferable delivery of the leucine-rich repeat domain of NLRX1 ameliorates lethal sepsis by regulating NF-κB and inflammasome signaling activation. (July 2021) - Koo, Ja-Hyun; Kim, Sang-Hun; Jeon, Soung-Hoo; Kang, Min-Jong; Choi, Je-Min
Abstract: Sepsis is an acute systemic inflammatory disease triggered by bacterial infection leading organ dysfunctions that macrophages are responsible for major triggering of systemic inflammation. Treatment options are limited to antibiotics and drugs to manage the symptoms of sepsis, but there are currently no molecular-targeted therapies. Here, we identified a novel macrophage-preferable delivery peptide, C10, which we conjugated to truncated domains of NLRX1 (leucine-rich repeat region (LRR), and nucleotide binding domain (NBD)) to obtain C10-LRR and C10-NBD. Leucine rich amino acid of C10 enables macrophage preferable moieties that efficiently deliver a cargo protein into macrophages in vitro and in vivo . C10-LRR but not C10-NBD significantly improved survival in an LPS-mediated lethal endotoxemia sepsis model. C10-LRR efficiently inhibited IL-6 production in peritoneal macrophages via prevention of IκB degradation and p65 phosphorylation. In addition, C10-LRR negatively regulated IL-1β production by preventing caspase-1 activation with a sustained mitochondrial MAVS level. Finally, co-treatment with anti-TNFα antibody and C10-LRR had a synergistic effect in an LPS-induced sepsis model. Collectively, these findings indicate that C10-LRR could be an effective therapeutic agent to treat systemic inflammation in sepsis by regulating both NF-κB and inflammasome signaling activation. Graphical abstract: Image 1